Forensic genetic value of a 27 Y-STR loci multiplex (Yfiler® Plus kit) in an Italian population sample. (March 2016) - Rapone, Cesare; D'Atanasio, Eugenia; Agostino, Alessandro; Mariano, Martina; Papaluca, Maria Teresa; Cruciani, Fulvio; Berti, Andrea
Highlights: 27 Y-STR haplotype data was obtained for 203 Italian subjects. Low and not significant genetic distances ( R ST ) were found among northern, central and southern Italians. The Island of Sardinia was clearly differentiated from other Italian regions. Abstract: The analysis of Y chromosome short tandem repeat (Y-STR) haplotypes provides important information that can be used for investigative purposes and in population studies. The Yfiler ® Plus PCR Amplification kit (Yfiler ® Plus, Thermo Fisher Scientific, Waltham, MA, USA) allows the multiplex amplification of 27 Y-STRs, including 7 rapidly mutating markers (RM Y-STRs). In this study, 203 unrelated males from Italy, which were subdivided into 4 different geographical groups (North, Center, South and Sardinia) were analyzed. Several intra-population diversity indexes were computed and compared to those obtained using only loci either from the minimal haplotype or the 17-plex (Yfiler ®, Thermo Fisher Scientific, Waltham, MA, USA). In addition, inter-population diversity analysis ( R ST ) among the four Italian samples was performed. The same analysis was also used to compare the Italian sub-sets to other European populations where the Yfiler ® Plus haplotype frequency data were available. The Sardinians were significantly differentiated from the other three Italian groups, thus requiring a specific sub-national Y-STR haplotype database. The Yfiler ® Plus kit showed a high power of discrimination which is useful for criminal investigations, principally due to the inclusion of RM Y-STRs.